Phenotypic clusters in heart failure with preserved and mid-range ejection fraction: new data and perspectives - O. V. Tsygankova; V. V. Veretyuk (Российский кардиологический журнал, 2021)
The problems of heart failure (HF) are becoming increasingly important every year due to the increasing spread of cardiovascular diseases resulting in its development, as well as the impact of metabolic factors, obesity, drugs and endocrine dysfunctions on the myocardium. Isolation of phenotypes with preserved, mid-ranged and reduced ejection fraction in HF allows ranking the evidence base and identifying groups of patients with preferred drug intervention strategies aimed at achieving the six goals of treating HF patients and, above all, reducing mortality. The results of recent studies have significantly expanded the list of tools for management of HF with reduced ejection fraction (EF), presented today, according to John J. V. McMurray, by five pillars: angiotensin-converting enzyme inhibitors or angiotensin-II receptor blockers, angiotensin receptor antagonist/neprilysin inhibitor, beta-blockers, mineralocorticoid receptor antagonists, sodium-glucose cotransporter 2 (SGLT2). On the other hand, the exceptional heterogeneity of patients with HF with preserved and mid-range EF and a prevailing opinion on the need for a unified therapy for patients with HF with mid-range and reduced EF, along with the absence of proven prognosis-modifying drugs, require the identifying phenotypic clusters of patients for targeted selection of a treatment strategy. This was the subject of interest in this literature review.